Causal genes identification of giant cell arteritis in CD4+ Memory t cells: an integration of multi-omics and expression quantitative trait locus analysis - Yu, Qiyi; Wu, Yifan; Ma, Xianda; Zhang, Yidong (Inflammation research, 2025)
Background Giant cell arteritis (GCA) is a prevalent artery and is strongly correlated with age. The role of CD4+ Memory T cells in giant cell arteritis has not been elucidated. Method Through single-cell analysis, we focused on the CD4+ Memory T cells in giant cell arteritis. eQTL analysis and mendelian randomization analysis identified the significant genes which have a causal effect on giant cell arteritis risk. CD4+ Memory T cells were subsequently divided into gene-positive and gene-negative groups, then further single-cell analysis was conducted. Mendelian randomization of plasma proteins, blood-urine biomarkers and metabolites were also performed. Eventually, the PMA induced Jurkat cell lines were used for biological experiments to explore the specific functions of significant causal genes in CD4+ Memory T cells. Results Similarity of CD4+ Memory T cells in GCA and old samples were explored. DDIT4 and ARHGAP15 were identified as significant risk genes via mendelian randomization. The CD4+ Memory T cells were then divided into DDIT4 ± or ARHGAP15 ± groups, and further single-cell analysis indicated the differences in aspects involving intercellular communication, functional pathways, protein activity, metabolism and drug sensitivity between positive and negative groups. In vitro experiments, including overexpression and knockdown, demonstrated that DDIT4 leading to a chronic, low-intensity inflammatory state in CD4+ Memory T cells, eventually promoting the development of GCA. Conclusion DDIT4 and ARHGAP15 have significant causal effects on giant cell arteritis risk. Specifically, DDIT4 exhibit pro-inflammatory effects on GCA via promotes chronic, low-intensity inflammatory in CD4+ Memory T cell.